THE SPECIFICS OF MANIFESTATIONS OF THE INTERRELATION POLITICAL AND LEGAL CONSCIOUSNESS AND DEVELOPMENT IDEOLOGY OF STATE-BUILDING IN THE TIMES OF THE ANCIENT EAST - Oleksandr V. Krasnokutsky (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the work. Investigate the specificity of manifestations of the interrelation political and legal consciousness, and, at the same time, the development of the ideology of state-building as a particular species of theoretically informed practical consciousness, which was used by the creators of state forms in the times of the Ancient East. Methodology. The study is based on the principles of materialist dialectics, historicism, formational and civilizational approaches. The scientific novelty. The obtained results of a study that summarize the scientific novelty can be formulated in the form of abstracts: a) identified two lines of ideological interaction on state building in the East in ancient times; b) formed a theoretical model of ideological matrix of state-building of the Ancient Orient; c) revealed, that the motility of this ideological matrix is consistent with the development of power in the state of those times. Conclusions. Specificity of manifestations of the interrelation political and legal consciousness and development ideology of state-building in the times of the Ancient East – is the existence of two lines of ideological interaction in the field of state-building in a state-organized society: the first line – the unilateral influence of political consciousness on the legal consciousness; the second line – the asymmetric inverse influence of legal consciousness on political consciousness. These two lines of ideological interaction (the unilateral influence of political consciousness on the legal consciousness and the asymmetric inverse influence of legal consciousness on political consciousness) have created original ideological matrix of state-building. Within this ideological matrix of state-building in the times of the Ancient East formed corresponding view ideological phenomenon – the ideology of state-building of oriental slave state.